Thermal behavior analysis of lithium-ion capacitors at transient high discharge rates. (September 2022) - Zhou, Wei; Liu, Zhien; An, Yabin; Luo, Maji; Zhang, Xiaohu; Song, Shuang; Li, Chen; Liu, Zehui; Gao, Yinghui; Zhang, Haitao; Zhang, Xiong; Sun, Xianzhong; et al.
Abstract: As one of the prospective high-rate energy storage devices, lithium-ion capacitors (LICs) typically incorporate non-Faradaic cathodes with Faradaic pre-lithiated anodes. LICs that deliver power density at high-rate discharging process can be accompanied by overheating problems which result in capacity deterioration and lifetime reduction. Therefore, it is essential to conduct a comprehensive analysis of the heat generation of LICs. The thermal behavior of pouch lithium-ion capacitors in this work is systematically investigated at transient high-rates from 1C to 550C. The heat transfer mechanisms of each part in the overall thermal behavior are quantified in detail during discharging processes. As the discharge rate increases, the temperature curve shows an upward parabolic trend at the end of discharge, with a maximum temperature of 33.68 °C at 200C.The proportion of irreversible heat to total heat generation is close to 80 % at 550C, but the temperature at the end of discharge decreases owing to the reduced discharge time. The actually measured temperature rise is compared with the one calculated using the intermittent current method, the voltage-current (VI) characteristic method and the alternating current impedance method. It can be found that the intermittent current method calculated temperature trends are in good agreement with the measured values better than other methods, because the polarization internal resistance is significantly related to the discharge time interval. These results would provide the basis for further development of a thermal model of the cell, in order to rationally design the cooling system to avoid overheating and degradation of the cells. Highlights: The thermal behavior of LICs at transient high-rates are systematically investigated. The terminal temperature curve shows an upward parabolic trend at different rates. The maximum temperature of 33.68 °C occurs at 200 °C. Three methods are used to characterize the internal resistance of LICs.